Trans-affirming care: An integrative review and concept analysis. (November 2021) - Lightfoot, Sophie; Kia, Hannah; Vincent, Alex; Wright, David Kenneth; Vandyk, Amanda
Abstract: Background: Contemporary healthcare exists within a cisnormative landscape which underpins the erasure of trans persons in healthcare, health research, and health education, and results in negative experiences and poorer outcomes. Further, nurses report feeling inadequately prepared to provide affirming care to trans patients, with little guidance available to inform their practice. Objective: To explore the conceptual understanding of trans-affirming care as it pertains to nursing, and to provide recommendations for trans-affirming nursing care at the systemic, organizational, and individual level. Methods: A systematic search of the literature was completed using standard review processes. Two reviewers independently applied a two-step study selection procedure to identify eligible citations. Walker and Avant's concept analysis method was used to analyze the extracted data to determine antecedents, defining attributes, empirical referents, and consequences. Results: Of the 5914 studies, 136 met criteria, representing a variety of clinical settings. The antecedents identified were depathologization of gender variance and cultural humility. The defining attributes were patient-led care, trans-affirming culture, and trans-competent providers. The consequences were improved psychological and physical health outcomes. Conclusions: Trans persons and communities are becoming more visible in society, as are their testimonials about their substandard treatment within healthcare systems. Nurses need to respond to these health inequities with self-reflection, advocacy, and education. At the center of this work is the concept of trans-affirming care, which is a philosophy of care specific to trans persons. Tweetable abstract: This article offers an evidence-informed definition of trans-affirming care and recommendations for how it can be operationalized by nurses.